Involvement of CB1R and CB2R Ligands in Sleep Disorders and Addictive Behaviors in the Last 25 Years - Marcel Pérez-Morales; Rodolfo Espinoza-Abad; Fabio García-García (Pharmaceuticals)
Over the last three decades, the decriminalization and legalization of therapeutic and recreational marijuana consumption have increased. Consequently, the availability of marijuana-based products associated with its therapeutic use has increased. These developments have stimulated research on cannabinoids involving a wide range of animal models and clinical trials. Also, it is reported that cannabinoids promote sleep in animal models and naïve human participants, and they seem to improve insomnia and sleep apnea in patients. However, evidence from rigorous clinical trials is needed. In addition, among several physiological processes, cannabinoid receptors modulate dopamine synthesis and release. In this regard, the side effects of marijuana and marijuana derivatives must not be ignored. The chronic consumption of marijuana could reduce dopamine responsivity, increase negative emotionality, and induce anhedonia. Research on the neurobiological changes associated with cannabinoid ligands in animal models, in regard to the consumption of both marijuana and marijuana-based compounds, must improve and the effectiveness of the therapeutic outcomes in clinical trials must be guaranteed. In this review, we include a detailed description of the mechanisms of action of cannabinoids on the brain and their impact on sleep disorders and addictive behaviors to emphasize the need to understand the potential risks and benefits of their therapeutic and recreational use. Evidence from basic research and clinical trials from papers published between 2000 and 2024 are included. The pharmacodynamics of these compounds is discussed in terms of sleep–wake regulation, drug addiction, and addictive behaviors.